1,2,3-Triazine 1-Oxides Are a Productive Platform for Synthetic Methodologies - De Angelis, Luca; Doyle, Michael P. (SynOpen, 2025)
This graphical review provides a concise overview of the synthesis and uses of 4-carboxylato-1,2,3-triazine 1-oxides in diverse syntheses, especially of heterocyclic compounds. Prepared in high yields from reactions between vinyldiazoacetates and tert-butyl nitrite, these triazines undergo nucleophilic substitution reactions, generally at the 6-position with the loss of dinitrogen or nitrous oxide, to form diverse products. Deoxygenation to 1,2,3-triazines, inverse-electron-demand Diels–Alder reactions, borohydride-induced 1,4-hydrogen addition, and syntheses of new diazo compounds are among the new processes that have been uncovered. This review serves as an indicator for future applications.
Keywords: nucleophilic addition; heterocycles; deoxygenation; cycloaddition; inverse-electron-demand Diels–Alder reaction; triazines; diazo compounds